5G IN HEALTHCARE FOR TELEMEDICINE - Kalra, Bhawana; Kumar, Deepak; Sharma, Shiafali (International Journal of Psychosocial Rehabilitation, 2020)
With advances in 5G technology, telemedicine is at the forefront of the changing healthcare landscape. This abstract clarifies the transformational impact of 5G in facilitating telemedicine, transforming patient care, and removing geographic barriers to deliver more convenient and quality healthcare services. The advent of 5G technology offers unprecedented potential in terms of high speed, seamless connectivity, and data transmission. These developments are a cornerstone for the advancement of telemedicine, overcoming the limitations of traditional healthcare delivery through real-time video consultation, remote assessment, and patient monitoring interacting with each other. This paper covers several aspects of telemedicine enabled by 5G. It explores the convenience of high-speed connectivity for seamless and immersive doctor-patient communication, ensuring timely access to health information regardless of geographic barriers The low latency characteristics of 5G enable real-time communication of medical data, increasing diagnostic accuracy, and enabling remote surgery and interventions. Additionally, the integration of 5G into telemedicine opens the door to new healthcare applications, including augmented reality (AR) and virtual reality (VR) experiences, and enables the medical industry to deliver interactive tools training, surgical planning, and patient education. But while the prospects for remote 5G-enabled medicine are promising, challenges remain. Issues around data privacy, security, compliance, and precise use of technology require careful consideration and effective solutions to ensure ethical and responsible use. In conclusion, the integration of 5G technology into telemedicine heralds a transformational era in healthcare. It is accelerating the growth of peripheral health services, improving outcomes among patients, reducing health disparities, and creating a future in which individuals have access to comprehensive, high-quality health care that increases regardless of location.